A Circularly Polarized Slotted Waveguide Antenna Array - Mohamed Elhefnawy (Applications of Modelling and Simulation, 2019)
The design of a novel circularly polarized X‒band Slotted Waveguide Antenna Array (SWAA) is proposed in this paper. The CST Microwave Studio (CST MWS) simulation results show that the simulated Axial Ratio (AR) is below 3 dB from 9.497 GHz to 9.676 GHz, or 1.86% relative bandwidth, with a minimum AR is 0.556 dB at 9.6 GHz. The simulated reflection coefficient is below ‒23 dB within the 3 dB AR bandwidth. The simulated antenna gain is 7.288 dB at 9.6 GHz.